2020
DOI: 10.1007/s10340-020-01267-x
|View full text |Cite
|
Sign up to set email alerts
|

Using camera-trapping to assess grape consumption by vertebrate pests in a World Heritage vineyard region

Abstract: Vertebrate pests cause significant economic loss in several agricultural crops worldwide; therefore, their populations are often controlled through culling. Correctly identifying the main species responsible for the damage is essential to avoid persecuting the wrong targets, yet it is challenging. During 2016 and 2017, we tested the usefulness of camera-trapping (CT) in Terceira Island, Azores, Portugal to identify vertebrate pests. Vineyard owners in this region cull the Azores woodpigeon (Columba palumbus az… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Our observations are in line with other studies in tropical agroforestry systems [ 9 , 41 , 58 , 72 ], which showed a strong correlation between insectivorous bird abundance and bird predation on artificial mimics. Together, these results counter common perceptions by farmers of birds being only pests of crops [ 10 , 73 ].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Our observations are in line with other studies in tropical agroforestry systems [ 9 , 41 , 58 , 72 ], which showed a strong correlation between insectivorous bird abundance and bird predation on artificial mimics. Together, these results counter common perceptions by farmers of birds being only pests of crops [ 10 , 73 ].…”
Section: Discussionmentioning
confidence: 57%
“…However, to what extent birds positively control insect pest in African subsistence farms remains mostly unknown. Many farmers perceive birds as pests [ 10 , 11 ]. Thus, it is extremely important that the net effect of birds as insect predators in farmlands is quantified.…”
Section: Introductionmentioning
confidence: 99%
“…Starlings were the most abundant bird species observed at the Whatcom County dairies each week. Despite the presence of other bird species that are known to be agricultural pests [36][37][38][39], starlings represented between 61% (week 3) and 90% (week 4) of all birds counted. The dominance of starlings as the most common avian pest species on Whatcom County dairies is consistent with previous data from surveys of Washington State dairy farmers [24,40].…”
Section: Discussionmentioning
confidence: 99%